Prolonged Adrenal Insufficiency After the Discontinuation of Mitotane Therapy - Muratori, Leonardo; Pia, Anna; Reimondo, Giuseppe; Pisano, Chiara; La Salvia, Anna; Puglisi, Soraya; Scagliotti, Giorgio V.; Sperone, Paola (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2020)
Introduction: Adrenocortical carcinoma (ACC) is a rare neoplasm characterized by a high risk of recurrence after radical resection. The role of adjuvant systemic therapy in radically resected patients is unclear. Mitotane, a steroidogenesis inhibitor, is the only drug approved for the systemic treatment of advanced ACC. In 2007, a retrospective case-control study provided the evidence that mitotane, administered for two years after successful surgery, could prolong recurrence-free survival. Adrenal insufficiency (AI), which occurs in almost all patients during the first 12 months of treatment, is an expected side effect of mitotane and requires steroid replacement therapy. Due to its long halflife, mitotane-induced AI persists several months after treatment discontinuation and is managed by cautious tapering of glucocorticoid replacement therapy. Results: We report a case of symptomatic AI diagnosed after a severe allergic reaction occurring three years after the discontinuation of adjuvant mitotane therapy. Conclusion: The case suggests that mitotane-induced AI should be monitored for a long time to asses full recovery of adrenal function, in order to prevent adrenal crises.
Keywords: treatment